“Ek sal en jy gaan.” The interaction between the modale auxiliaries sal and gaan - Wierenga, Roné (Stellenbosch Papers in Linguistics Plus, 2023)
Traditionally sal, wil, moet and kan are regarded as the most common modal auxiliaries in Afrikaans.  Recent literature has acknowledged that gaan, a lexical verb denoting ‘movement away from a deictic centre’, has acquired modal functions resembling those of sal in specific contexts. This article aims to explore the development of the grammatical functions of gaan and the interchangeability of sal and gaan as modal auxiliaries within the scope of grammaticalisation theory. A corpus study is undertaken to identify and analyse the nuances in the modal functions for which these auxiliaries compete when expressing modality in order to establish the extent to which gaan has grammaticalised. Similarly, the degree to which gaan and sal can be used as synonyms is explored in the formal register of the Taalkommissie’s newspaper sub-corpus and the informal register of the News Commentary corpus.